Regional political risk analysis: The conflict in the Niger Delta and its impact on the political risk of the Gulf of Guinea - Bischoff, Emil Gottfried (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.